KARAKTERISASI FRAGMEN DNA GEN GLUKOAMILASE (GLU1) PRODUK PCR DENGAN ANALISIS RESTRIKSI - Sofijan Hadi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
Characterization used retriction enzyme on the 1784 bp (base pairs) DNA fragmen of glucoamylase gene (GLUI) of E. fibuligera ITB. R. cc. 64 has been done. The rectriction enzyme usage was Stu 1, Eco RI, Eco RV, Bam HI and Sau 3A. The purpose of this research were: First was to know recognition site of 1784 bp DNA fragmen of glucoamylase gene (GLUI) by the restriction enzyme above. The second was to know homologyst the glucoamylase gene (GLUI) E. fibuligera ITB. R. cc. 64 and the glucoamylase gene (GLUI) Saccharomycopsis fibuligera HUT 7212 (pSf GLUI). The result of amplification glucoamylase gene (GLUI) indicated that 1784 bp DNA fragmen on GLUI locus has succesfully isolated and gave the same size with the positive control pSf GLUI. Analysis of those DNA fragmen by StuI, Eco RV, Eco RI, Bam HI and Sau 3A indicated that 1784 bp of DNA fragmen from E. fibuligera ITB.R.cc.64. has the same result with 1784 bp of DNA fragmen from pSf GLUI. The result of the fragments after incubated by restriction enzymes are as follows: ± 997 bp and 787 bp by Eco RI, 1000 bp and 1780 bp by Bam H) and 850 bp and 760 bp by Sau 3A. Digestion using StuI and Eco RI was failed. To ensure that the DNA fragmen 1784 bp has characteristic as glucoamylase gene, it should be expressed into S. cerevisiae and/or should be determined the nucleotide sequence by DNA sequencing.